Stress concentration factors for flat bars with projection under uniaxial loading - Fu, Ming Han. (2008)
The boundary element method for two-dimensional elastostatics has been used to obtain stress concentration factor values for flat ‘T’ shaped components subjected to uniaxial loading with remote restraints being applied. Parametric studies involving geometric variation for flat bars with different projection have been carried out. This is to determine the optimum configuration that will lead to better design of the structural and machine components. The computational results obtained were compared with analytical data in open literature wherever possible. Generally they are found to be in good agreement. The results show that maximum stress occurs in the middle section of the fillet. By increasing the ratio of fillet radius to shank depth, it is noticed that there is a decrease in stress concentration factor.